A procedure for evaluating seismic energy demand of framed structures. - Chou, Chung-Che (Earthquake engineering & structural dynamics.)
Energy serves as an alternative index to response quantities like force or displacement to include the duration related seismic damage effect. A procedure fo evaluate the absorbed energy in a multistorey frame from energy spectra was developed. For low to medium rise frames, it required a static pushover analysis of the structure to determine the modal yield force and ductility factor of an equivalent single degree of freedom system for the first two modes. The energy spectra were then used to determine the energy contribution of each mode. A procedure was also developed to distribute the energy along the frame height based on energy shapes. This study showed that the second mode response in some cases needs to be considered to reflect the energy (or damage) concentration in the upper floors.